When soldiers say no selective conscientious objection in the modern military - Ellner, Andrea; Robinson, Paul; Whetham, David (Military and defence ethics)
A decade of conflict not clearly aligned to vital national interests combined with recent acts of selective conscientious objection by members of the military have led some to reappraise the distinction between absolute and selective conscious objection, and argue that selective conscientious objection ought to be legally recognised and permitted.